Vascular Acrosyndromes Associated With Prolonged Tumor Response in Advanced Lung Cancer Patients During Treatment With Antimetabolites: A Report of Two Cases - Geier, Margaux; Babey, Hélène; Monceau-Baroux, Lucie; Quéré, Gilles; Descourt, Renaud; Cornec, Divi; Robinet, Gilles (Frontiers in Oncology, 2021)
Background: Pemetrexed and gemcitabine are both antimetabolites drugs approved in solid tumors including non-small cell lung cancer (NSCLC). Their toxicity profile is well known. However, rare vascular side effects can occur such as vascular acrosyndromes and especially digital ischemia. The cause of this disfiguring and painful event is still controversial. Amputation is frequently required and has been described as a predictor of poor survival outcomes. Case Presentation: This report presents two cases of vascular acrosyndrome in NSCLC cancer patients during treatment with antimetabolites (pemetrexed and gemcitabine). Patients presented severe digital ischemia having required prostacyclin analogue and chemotherapy discontinuation. In one case, symptoms improved while in the other case symptoms persisted. Both patients experienced prolonged tumor response. These findings suggest a multifactorial mechanism behind digital necrosis including an autoimmune process, which could lead to prolonged tumor control as described with immune checkpoint inhibitors. Conclusion: Severe vascular acrosyndrome such as digital ischemia can occur in lung cancer patients treated with antimetabolites. These drugs should be used with caution in patients with predisposing factors. Prolonged tumor response may be observed when immune vascular side effects occur, but this association needs further investigations.